Imagery is like perception: three perceptual effects produced with color imagery - Cochrane, Brett (My University, 2019)
Investigations of visual imagery are as old as documented scientific inquiry. Despite this, there is still little understanding of how visual imagery interfaces with our perceptual world. In the present thesis, I investigated three perceptual effects to evaluate whether they were influenced by color imagery. The first effect is an inter-trial priming effect known as the Priming of Pop-out (PoP) effect that constitutes faster responding when the target and distractor colors are repeated than when they are switched across trials of visual search. Here, it was demonstrated that when color imagery was put in opposition with the color of previous target, a pattern of results emerged that was opposite that of the PoP effect – suggesting that color imagery interacted with the representations typically driving the PoP effect. The second effect were those associated with stimulus-response (S-R) bindings, often termed event file binding effects. In a typical event file procedure, it is demonstrated that performance is efficient when an arbitrary key-press is made in response to color stimuli that either completely match or mismatch the S-R bindings of a following two-alternative force choice (2AFC) task, and inefficient when there is partial overlap between these S-R bindings. We demonstrated that color imagery bound to arbitrary responses could produce quite similar effects on a 2AFC color discrimination task as those produced by perceptual colored stimuli. The last effects were the facilitation and inhibition effects observed across trials of 2AFC tasks when targets are presented in the same location. Here it was demonstrated that both perceptual and imagined colored targets led to fast responding when they matched perceptual color targets on the following trial than when they mismatched. When an irrelevant task intervened between these targets, the opposite pattern of results was observed; responses were slower when either the imagined or perceptual targets matched than when they mismatched. This suggests that color imagery could produce priming or habituation-like effects much like perceptual colors. Overall, the present thesis supports the idea that color imagery can influence many of the processes guiding our behavior in the perceptual world.